Lead-free halogen-free no-clean copper paste as well as preparation method and application thereof

By developing lead-free, halogen-free, no-clean-free copper solder paste, the problem of residue after welding is solved by using modified copper powder and specific organic components, the problem of residue-free and good patch performance after welding is achieved, product reliability is improved and cost and pollution is reduced.

CN119681492AActive Publication Date: 2025-03-25BEIJING QINGLIAN TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411642190.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-25
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Existing welding materials are difficult to completely clean after welding, and the residue affects electrical performance and product quality reliability. At the same time, cleaning agents increase environmental pollution and production costs.

Method used

A lead-free, halogen-free, no-cleanless copper solder paste is developed, containing 75~80 parts of modified copper powder and 20~25 parts of organic components. Through surface modification treatment and organic components of specific formulas, we can achieve residual-free and good patch performance after welding.

Benefits of technology

It achieves residue-free after welding, improves product reliability and stability, reduces production costs, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681492A_ABST
    Figure CN119681492A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-performance device packaging, in particular to lead-free halogen-free no-clean copper paste and a preparation method and application thereof. The no-clean copper paste provided by the invention does not contain lead or halogen, has no residue after welding, is no-clean and has good stability. The no-clean copper paste provided by the invention is good in oxidation resistance and can be subjected to hot pasting after being dried, so that the problem of chip displacement in the transferring and sintering process after chip pasting is effectively avoided; after the copper paste is sintered, the internal structure is uniform, the phenomena of cracks, holes and the like are avoided during super sweeping, defects are effectively avoided, and the copper paste has high strength; in addition, a drying structure is uniform in structure after being sintered, no obvious defect exists, and the actual production requirement can be well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance device packaging, and in particular to a lead-free, halogen-free, and cleaning-free copper paste, and a preparation method and application thereof. Background Art

[0002] With the rapid development of third-generation wide bandgap semiconductors and surface mount electronic component welding technology, the industry's requirements for their reliability are getting higher and higher. At the same time, with the development of the semiconductor industry, the performance and quality requirements for solder pastes for low-temperature interconnection and high-temperature service are also increasing. Compared with solder paste, copper paste has a higher melting point after sintering, and still has good reliability above 350°C, and there is no risk of chip separation from the substrate. In order to increase the service life of electronic products, cleaning agents based on fluorinated and chlorinated solvents are usually used for cleaning, but the cleaning agents currently used are difficult to completely clean, and these residues will lead to unsatisfactory electrical performance and affect the reliability of product quality. At the same time, the use of cleaning agents will pollute the environment and increase production costs.

[0003] Existing welding materials mostly use wet bonding process for reflow soldering, which inevitably leaves residual organic matter overflowing onto the substrate after soldering. This method can have high production efficiency for chip or pin soldering, but for system-level chip packaging, it is easy to make the organic matter difficult to volatilize, resulting in gas escape channels in the sintered body, which has an adverse effect on product quality and reliability.

[0004] At present, it is urgent to invent a no-clean copper paste and develop a patch process to improve product reliability, reduce costs and improve production efficiency. In view of this, the present invention is proposed. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a lead-free, halogen-free, and clean-free copper solder paste, and a preparation method and application thereof. The solder paste has no residue after soldering and has good patch performance.

[0006] Specifically, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a copper solder paste comprising 75 to 80 parts by mass of modified copper powder and 20 to 25 parts by mass of an organic component; wherein, based on the total amount of the organic component as 100%, the paste comprises 1% to 3% of a thixotropic agent, 0.5% to 2% of a dispersant, 0.1% to 0.5% of an antioxidant, 0.3% to 0.8% of a binder, 0.5% to 2% of a leveling agent, 0.5% to 1% of an adhesion promoter, and 90.7% to 97.1% of a solvent.

[0007] Preferably, the modified copper powder is obtained by treating copper powder with a surface modifier; the particle size of the copper powder is 2-10 μm; and the surface modifier is a compound containing a functional group that forms a coordination bond with copper ions.

[0008] Preferably, the surface modifier is phthalic acid or its salt, oleic acid or its salt, folic acid or its salt; the surface modification method is: the surface modifier is configured into a 0.1%-1% surface modification solution, and then the copper powder is placed in the surface modification solution for full contact; the mass ratio of the copper powder and the surface modification solution is 1:2~10; the full contact time is 0.5~2h.

[0009] Preferably, the thixotropic agent is selected from at least one of modified castor oil, polyamide wax, fumed silica, and organic bentonite, preferably modified castor oil and / or polyamide wax.

[0010] Preferably, the dispersant is selected from at least one of ethanol, ethylene glycol, diethylene glycol, cyclohexanol, isopropanol, glycerol and n-butanol, preferably diethylene glycol or glycerol.

[0011] Preferably, the antioxidant is selected from at least one of 2-mercaptobenzothiazole, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 1,3,5-tri(phenylamino)benzene, and 5-tri(phenylamino)benzene, and is optimized to be 2-mercaptobenzothiazole or 2,6-di-tert-butyl-p-cresol.

[0012] Preferably, the binder is selected from at least one of cellulose acetate, sodium carboxymethyl cellulose, carboxymethyl cellulose, polyethylene carbonate, and polypropylene carbonate, preferably carboxymethyl cellulose and / or polypropylene carbonate.

[0013] Preferably, the leveling agent is selected from at least one of polydimethylsiloxane, polymethylalkylsiloxane, organic modified polysiloxane, polyether modified polysiloxane, acrylate copolymer, and fluorine modified acrylate copolymer, preferably polyether modified polysiloxane or acrylate copolymer.

[0014] Preferably, the adhesion promoter is selected from at least one of titanate, aminosilane, and phosphate, preferably titanate.

[0015] Preferably, the solvent is selected from at least one of N-methylpyrrolidone, diethylene glycol monoethyl ether acetate, propylene carbonate, 1,4-dioxane, N,N-dimethylformamide, DMF, caprolactone, ethyl acetate, ethylene glycol ether, a mixture of dimethyl glutarate and dimethyl adipate, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and ethylene glycol phenyl ether, preferably diethylene glycol dimethyl ether, ethylene glycol phenyl ether and N-methylpyrrolidone.

[0016] In the second aspect, the present invention provides a method for preparing the copper solder paste, comprising the following steps: mixing a dispersant, an antioxidant, a binder and a solvent under a temperature condition of 50°C to 80°C; cooling the mixture to 40°C to 50°C, and then mixing it with a thixotropic agent; further cooling the mixture to 20°C to 30°C, and then mixing it with a leveling agent and an adhesion promoter; and then mixing the mixture with modified copper powder.

[0017] Preferably, the preparation method of the modified copper powder comprises: mixing the copper powder and the surface modification solution in a mass ratio of 1:2-10, stirring for reaction for 30-60 minutes; centrifuging at 4500-6000 r / min for 5-10 minutes to remove the surface modification solution; and vacuum drying at 50-80° C. for 5-8 hours.

[0018] Preferably, when the mixed material is mixed with the modified copper powder, the mixing speed is 1000-1200 r / min and the mixing time is 10-15 min.

[0019] In a third aspect, the present invention provides application of the copper solder paste or the copper solder paste prepared by the preparation method in power device packaging.

[0020] As one of the more specific implementations, the present invention provides a method for mounting a lead-free, halogen-free, and clean-free copper paste for power device packaging, comprising the following steps: a) The copper solder paste or the copper solder paste prepared by the preparation method is evenly coated on the front side of the substrate by printing to obtain a stacking structure of the solder paste and the substrate.

[0021] b) placing the substrate after printing the copper paste in a drying oven for drying to obtain a pre-dried copper paste substrate.

[0022] c) Using a thermal mounting machine to mount the chip on the pre-dried copper paste substrate to obtain a pre-sintered module.

[0023] d) placing the pre-sintered module in a vacuum or inert atmosphere for sintering to obtain a power device packaging structure.

[0024] Preferably, in step a), the printing thickness is 50-150 μm.

[0025] Preferably, in step b), the drying furnace uses air, vacuum or inert gas atmosphere for drying, the drying temperature is 90-110° C., and the drying time is 10-20 min.

[0026] Preferably, in step c), the size of the patch chip is 1*1~5*5mm, the temperature of the lower substrate of the thermal bonding machine is 70-90°C, the temperature of the upper pressure head is 130°C-150°C, and the patch pressure is 5-8kg.

[0027] Preferably, in step d), the sintering conditions are: sintering temperature 180° C.-280° C., sintering pressure 2-20 MPa, and sintering time 3-5 min.

[0028] Beneficial effects: The present invention provides a lead-free, halogen-free, and cleaning-free copper paste, and a preparation method and application thereof. The copper paste comprises 75-80 parts by mass of modified copper powder and 20-25 parts by mass of organic components; wherein, based on the total amount of the organic components as 100%, it comprises 1%-3% of a thixotropic agent, 0.5%-2% of a dispersant, 0.1%-0.5% of an antioxidant, 0.3%-0.8% of a binder, 0.5%-2% of a leveling agent, 0.5%-1% of an adhesion promoter, and 90.7%-97.1% of a solvent. The cleaning-free copper paste provided by the present invention is lead-free and halogen-free, has no residue after welding, is cleaning-free, and has good stability. The clean-free copper paste provided by the present invention has good oxidation resistance and can be hot-mounted after drying, effectively avoiding the problem of chip displacement during transportation and sintering after chip mounting; and the internal structure of the copper paste after sintering is uniform, and there is no cracking, holes and the like in ultra-scanning, which effectively avoids the generation of defects and has high strength; in addition, the dried structure has a uniform structure after sintering without obvious defects, and can well meet actual production needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be described below.

[0030] Figure 1 Schematic diagram of the process flow for using lead-free, halogen-free, and no-clean copper paste for power device packaging.

[0031] Figure 2 This is a white light interference image of the lead-free, halogen-free, and clean-free copper paste provided in Example 1 of the present invention after printing.

[0032] Figure 3 This is a schematic diagram of chip packaging.

[0033] Figure 4 This is an ultrasonic scanning image of a module of the lead-free, halogen-free, and clean-free copper paste provided in Example 1 of the present invention after chip mounting and sintering. DETAILED DESCRIPTION

[0034] The present invention provides a lead-free, halogen-free, and cleaning-free copper paste for power device packaging, which is free of cleaning after welding, has good storage stability, good printing performance, excellent sintering performance, is lead-free, and meets the environmentally friendly halogen-free standards of the EU RoHS directive. The present invention also provides a method for using a copper paste patch for power device packaging, which can effectively prevent the problem of chip displacement and crushing during the sintering process.

[0035] The technical solution provided by the present invention specifically includes the following contents: First, the present invention provides a lead-free, halogen-free, and cleaning-free copper paste, comprising the following raw materials in percentage by weight: 75-80% of surface-modified copper particles and 20-25% of an organic solvent system. The organic solvent system comprises the following components in percentage by weight: 1% to 3% of a thixotropic agent, 0.5% to 2% of a dispersant, 0.1% to 0.5% of an antioxidant, 0.3% to 0.8% of a binder, 0.5% to 2% of a leveling agent, 0.5% to 1% of an adhesion promoter, and 90.7% to 97.1% of a solvent.

[0036] In the present invention, the copper particles are treated on the surface of the copper particles by compounds; specifically, the morphology of the copper particles is a mixture of spherical, quasi-spherical or flaky; the particle size of the copper particles is 2-10μm, preferably 2-5μm, and more preferably 2-4μm, for example 2μm, 3μm, 4μm.

[0037] In the present invention, the surface modifier is selected from compounds containing functional groups that form coordination bonds with copper ions; including: carboxyl, hydroxyl, amino, aldehyde, nitro, thiol, sulfonic acid, phosphoric acid, cyano, chloro, bromo and iodo, etc., and one or more of the above can be selected. Among them, carboxyl is particularly preferred. In addition, the number of functional groups that can form coordination bonds with copper ions constituting the polar compound can be more than one. In particular, it is most ideal to have one or two functional groups that can form coordination bonds with copper ions.

[0038] In the present invention, the surface modifier is selected from at least one compound containing a carboxyl group, preferably phthalic acid, 1,2-cyclohexane dicarboxylic acid, 4-cyclohexene-1,2-dioic acid, 1,1-cyclohexane dicarboxylic acid, 2,2'-biphenyl dicarboxylic acid, octanoic acid, decanoic acid, oleic acid and folic acid. It is desirable to select one or more from this group, among which phthalic acid, oleic acid and folic acid are more preferred. In addition, their salts (such as sodium or potassium salts) can be used, such as disodium phthalate, sodium octanoate, sodium decanoate, sodium oleate.

[0039] In the present invention, the surface modification treatment method for the copper powder can be selected from solid phase surface modification treatment method, liquid phase surface modification treatment method, gas phase surface modification treatment method, preferably liquid phase surface modifier treatment method.

[0040] In the present invention, the surface modification solution is prepared by mixing a surface modifier and a solvent (selectively ethanol, ethylene glycol, propylene glycol, 1,3-propylene glycol, etc., preferably at least one of ethanol and ethylene glycol) in a mass ratio of surface modifier: solvent (0.1-1): (99-99.9), preferably a ratio of 0.3:99.7 to prepare the surface modification solution.

[0041] The surface modification of copper powder can be carried out using a centrifuge, an oscillator, a magnetic stirrer or other homogenizing equipment. The surface modification solution and copper particles are mixed in a mass ratio of 1:2; 1:5; 1:10, preferably 1:5, and the treatment time is 0.5h-2h.

[0042] The thixotropic agent is selected from modified castor oil, polyamide wax, fumed silica, organic bentonite, etc., preferably one or both of modified castor oil and polyamide wax.

[0043] The dispersant is selected from at least one of ethanol, ethylene glycol, diethylene glycol, cyclohexanol, isopropanol, glycerol and n-butanol, preferably diethylene glycol or glycerol.

[0044] The antioxidant is selected from one or more of 2-mercaptobenzothiazole, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 1,3,5-tri(phenylamino)benzene; 5-tri(phenylamino)benzene, etc., and is optimized to be 2-mercaptobenzothiazole and 2,6-di-tert-butyl-p-cresol.

[0045] The binder is selected from at least one of cellulose acetate, sodium carboxymethyl cellulose, carboxymethyl cellulose, polyethylene carbonate and polypropylene carbonate, preferably carboxymethyl cellulose or polypropylene carbonate.

[0046] The leveling agent is selected from at least one of polydimethylsiloxane, polymethylalkylsiloxane, organic modified polysiloxane, polyether modified polysiloxane, acrylate copolymer, and fluorine modified acrylate copolymer, preferably polyether modified polysiloxane or acrylate copolymer.

[0047] The adhesion promoter is selected from at least one of titanate, aminosilane, and phosphate, preferably titanate.

[0048] The solvent is preferably selected from one or more of N-methylpyrrolidone, diethylene glycol monoethyl ether acetate, propylene carbonate, 1,4-dioxane, N,N-dimethylformamide, DMF, caprolactone, ethyl acetate, ethylene glycol ether, a mixture of dimethyl glutarate and dimethyl adipate, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and ethylene glycol phenyl ether, preferably diethylene glycol dimethyl ether, ethylene glycol phenyl ether or N-methylpyrrolidone.

[0049] The present invention does not particularly limit the sources of the above components, and any conventional commercially available raw materials in the art can be used.

[0050] Furthermore, the preparation method of the lead-free, halogen-free, and clean-free copper paste comprises the following steps: S1. performing surface modification treatment on the copper powder and drying the copper powder to obtain the surface modified copper powder.

[0051] S2. Add a dispersant, an antioxidant, a binder and a solvent into a reaction container, heat to 50° C. to 80° C. and stir.

[0052] S3. Cool down to 40℃~50℃, add thixotropic agent into the reactor and stir evenly to fully activate it.

[0053] S4. Continue to cool down to 20°C to 30°C, add a leveling agent and an adhesion promoter into the reactor and stir evenly to obtain an organic solvent system.

[0054] S5. The copper powder treated by S1 is mixed, stirred, dispersed, canned, etc. with the mixed organic solution of S4 to obtain the lead-free, halogen-free, and cleaning-free copper paste.

[0055] Specifically and preferably, step S1 includes: S11. The copper powder and the surface modification solution are mixed in a mass ratio of 1:5, and stirred thoroughly with a stirrer. The reaction time is 30-60 minutes.

[0056] S12. The surface-modified copper powder is centrifuged at a speed of 4500-6000 r / min for 5-10 min to remove the surface modification solution, and the copper powder is dried by vacuum drying.

[0057] In step S12, vacuum drying is performed to obtain uniformly dispersed copper powder.

[0058] In step S5., a stirrer is used at 1000-1200 r / min for 10-15 min to obtain a mixed copper paste, which is further canned using a canning machine.

[0059] The present invention also provides application of the lead-free, halogen-free, and cleaning-free copper paste in high-power devices.

[0060] The present invention also provides a method for mounting a lead-free, halogen-free, and clean-free copper paste for power device packaging, comprising the following steps: a) The lead-free, halogen-free, and clean-free copper paste is uniformly coated on the front side of the substrate by printing to obtain a stacking structure of the solder paste and the substrate.

[0061] b) placing the substrate after printing the copper paste in a drying oven for drying to obtain a pre-dried copper paste substrate.

[0062] c) Using a thermal mounting machine to mount the chip on the pre-dried copper paste substrate to obtain a pre-sintered module.

[0063] d) placing the pre-sintered module in a vacuum or inert atmosphere for sintering to obtain a power device packaging structure.

[0064] Specifically and preferably, in step a), the printing thickness is 50-150μm. In step b), the drying furnace uses air, vacuum or inert gas atmosphere for drying, the drying temperature is 90-110℃, and the drying time is 10-20min. In step c), the size of the patch chip is 1*1~5*5mm, the temperature of the lower substrate of the thermal bonding machine is 70-90℃, the temperature of the upper pressure head is 130℃-150℃, and the patch pressure is 5-8kg. In step d), the sintering conditions are: sintering temperature 180℃-280℃, sintering pressure 2-20Mpa, and sintering time 3-5min.

[0065] The invention uses polypropylene carbonate or carboxymethyl cellulose to replace a large amount of rosin or acrylic resin in traditional solder, and while ensuring adhesion, prevents overflow of the binder during the sintering process, improves sintering stability, and improves the problem of uneven distribution of the binder due to solvent volatilization during welding, which leads to overscan defects. The invention uses titanate as an adhesion promoter to effectively solve the problem of poor chip mounting performance during thermal mounting and the risk of chip fragmentation due to chip displacement during the sintering process. In addition, the invention uses a carboxyl organic acid to modify the surface of the copper powder, which can improve the sintering activity and reduce the sintering porosity. The antioxidant 2-mercaptobenzothiazole is used to improve storage stability. Modified castor oil and polyamide wax are used as thixotropic agents to prevent the problem of solder paste sedimentation. In addition, the solvent in the invention is compounded according to a weight ratio using at least one of diethylene glycol dimethyl ether, ethylene glycol phenyl ether or N-methyl pyrrolidone, which can effectively control the solvent volatilization rate, improve the sintering quality, and reduce sintering defects.

[0066] The cleaning-free copper paste of the invention contains no lead and no halogen, has very little residue after welding, is cleaning-free, non-corrosive, and has good stability.

[0067] The present invention further proposes a chip mounting method, which can prevent chip displacement during the sintering process and prevent the sintering cavity from being polluted and the sintering body from being generated with gas escape channels due to the volatilization of a large amount of organic matter during the sintering process.

[0068] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] The endpoints and any values ​​of the ranges disclosed in this specification are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0070] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0071] In the examples provided in this specification, if no specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0072] In the following examples and comparative examples: the lead-free, halogen-free, and clean-free copper paste comprises the following components by weight percentage: 75% copper powder and 25% organic component. The copper powder used in the examples and comparative examples is copper powder treated with a phthalic acid surface modifier and has a D50 of 2 μm.

[0073] Examples 1-5 Examples 1-5 respectively provide a lead-free, halogen-free, and clean-free copper paste, and the specific formula and specific implementation amount (unit: %) of their respective organic components are shown in Table 1 below.

[0074] The preparation method of the lead-free, halogen-free, and clean-free copper paste comprises the following steps: S1. performing surface modification treatment on the copper powder and drying the copper powder to obtain the surface modified copper powder.

[0075] S2. Add a dispersant, an antioxidant, a binder and a solvent into a reaction container, heat to 50° C. to 80° C. and stir.

[0076] S3. Cool down to 40℃~50℃, add thixotropic agent into the reactor and stir evenly to fully activate it.

[0077] S4. Continue to cool down to 20°C to 30°C, add a leveling agent and an adhesion promoter into the reactor and stir evenly to obtain an organic solvent system.

[0078] S5. The copper powder treated by S1 is mixed, stirred, dispersed, canned, etc. with the mixed organic solution of S4 to obtain the lead-free, halogen-free, and cleaning-free copper paste.

[0079] Specifically, step S1 includes: S11. The copper powder and the surface modification solution are mixed in a mass ratio of 1:5, and stirred thoroughly with a stirrer. The reaction time is 30-60 minutes.

[0080] S12. The surface-modified copper powder is centrifuged at a speed of 4500-6000 r / min for 5-10 min to remove the surface modification solution, and the copper powder is dried by vacuum drying.

[0081] In step S12, vacuum drying is performed to obtain uniformly dispersed copper powder.

[0082] In step S5., a stirrer is used at 1000-1200 r / min for 10-15 min to obtain a mixed copper paste, which is further canned using a canning machine.

[0083] Comparative Examples 1-5 Comparative Examples 1-5 respectively provide a lead-free, halogen-free, and clean-free copper paste, and the specific formula and specific implementation amount (unit: %) of their respective organic components are shown in Table 2 below.

[0084] The preparation method of the lead-free, halogen-free, and clean-free copper paste is the same as that of the above-mentioned embodiment.

[0085] Experimental Example 1 The copper pastes prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were tested for performance under standard test conditions. The test results are shown in Table 3.

[0086] As shown in Table 3, the lead-free, halogen-free, and cleaning-free copper pastes provided by the embodiments of the present invention all show good performance in terms of solder paste stability, patch performance, and printing flatness, and are generally better than the comparative examples. The best performing ones among the embodiments are Embodiment 1 and Embodiment 3, which are lead-free and halogen-free, have no residue after soldering, are cleaning-free, are stable in storage, have excellent patch performance, good printing flatness, and have excellent reliability and stability.

[0087] After testing, the present invention uses polypropylene carbonate or carboxymethyl cellulose to replace a large amount of rosin or acrylic resin in traditional solder, while ensuring adhesion, preventing the overflow of the binder during the sintering process, improving the sintering stability, and improving the uneven distribution of the binder due to the solvent volatilization process during welding, resulting in overscan defects; the present invention uses titanate as an adhesion promoter to effectively solve the poor chip patch performance during the hot mounting process and the risk of chip fragmentation due to chip displacement during the sintering process; in addition, the present invention uses a carboxyl organic acid to modify the surface of the copper powder, which can improve the sintering activity and reduce the sintering porosity; the antioxidant 2-mercaptobenzothiazole is used to improve the storage stability; modified castor oil and polyamide wax are used as thixotropic agents to prevent the problem of solder paste sedimentation; in addition, the solvent in the present invention is compounded according to a weight ratio using at least one of diethylene glycol dimethyl ether, ethylene glycol phenyl ether or N-methyl pyrrolidone, which can effectively control the solvent volatilization rate, improve the sintering quality, and reduce sintering defects.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A copper solder paste, characterized in that: It includes 75-80 parts by mass of modified copper powder and 20-25 parts by mass of organic components; wherein, based on the total amount of the organic components as 100%, it includes 1%-3% of thixotropic agent, 0.5%-2% of dispersant, 0.1%-0.5% of antioxidant, 0.3%-0.8% of binder, 0.5%-2% of leveling agent, 0.5%-1% of adhesion promoter and 90.7%-97.1% of solvent.

2. The copper solder paste according to claim 1, characterized in that: The modified copper powder is obtained by treating copper powder with a surface modifier; the particle size of the copper powder is 2-10 μm; and the surface modifier is a compound containing a functional group that forms a coordination bond with copper ions.

3. The copper solder paste according to claim 2, characterized in that: The surface modification method is: the surface modifier is prepared into a 0.1%-1% surface modification solution, and then the copper powder is placed in the surface modification solution for full contact; the mass ratio of the copper powder and the surface modification solution is 1:2~10; the full contact time is 0.5~2h.

4. The copper solder paste according to any one of claims 1 to 3, characterized in that: The thixotropic agent is selected from at least one of modified castor oil, polyamide wax, fumed silica, and organic bentonite, preferably modified castor oil and / or polyamide wax; and / or, the dispersant is selected from at least one of ethanol, ethylene glycol, diethylene glycol, cyclohexanol, isopropanol, glycerol and n-butanol, preferably diethylene glycol or glycerol; And / or, the antioxidant is selected from at least one of 2-mercaptobenzothiazole, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 1,3,5-tri(phenylamino)benzene, and 5-tri(phenylamino)benzene, and is optimized to be 2-mercaptobenzothiazole or 2,6-di-tert-butyl-p-cresol; and / or, the binder is selected from at least one of cellulose acetate, sodium carboxymethyl cellulose, carboxymethyl cellulose, polyethylene carbonate, and polypropylene carbonate, preferably carboxymethyl cellulose and / or polypropylene carbonate; and / or, the leveling agent is selected from at least one of polydimethylsiloxane, polymethylalkylsiloxane, organic modified polysiloxane, polyether modified polysiloxane, acrylate copolymer, fluorine modified acrylate copolymer, preferably polyether modified polysiloxane or acrylate copolymer; and / or, the adhesion promoter is selected from at least one of titanate, aminosilane, and phosphate, preferably titanate; And / or, the solvent is selected from at least one of N-methylpyrrolidone, diethylene glycol monoethyl ether acetate, propylene carbonate, 1,4-dioxane, N,N-dimethylformamide, DMF, caprolactone, ethyl acetate, ethylene glycol ether, a mixture of dimethyl glutarate and dimethyl adipate, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and ethylene glycol phenyl ether, preferably diethylene glycol dimethyl ether, ethylene glycol phenyl ether and N-methylpyrrolidone.

5. The method for preparing the copper solder paste according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing a dispersant, an antioxidant, a binder and a solvent at a temperature of 50 to 80° C.; cooling the mixture to 40 to 50° C. and mixing it with a thixotropic agent; further cooling the mixture to 20 to 30° C. and mixing it with a leveling agent and an adhesion promoter; and mixing the mixture with modified copper powder.

6. The preparation method according to claim 5, characterized in that: The preparation method of modified copper powder includes: mixing copper powder and surface modification solution in a mass ratio of 1:2-10, stirring and reacting for 30-60 minutes; centrifuging at 4500-6000 r / min for 5-10 minutes to remove the surface modification solution; and vacuum drying at 50-80°C for 5-8 hours.

7. The preparation method according to claim 5 or 6, characterized in that: When the mixed material is mixed with the modified copper powder, the mixing speed is 1000-1200r / min and the mixing time is 10-15min.

8. Use of the copper solder paste according to any one of claims 1 to 4 or the copper solder paste prepared by the preparation method according to any one of claims 5 to 7 in power device packaging.

9. A method for mounting lead-free, halogen-free, and clean-free copper paste for power device packaging, characterized in that: The steps include: a) uniformly coating the copper solder paste according to any one of claims 1 to 4 or the copper solder paste prepared by the preparation method according to any one of claims 5 to 7 on the front side of the substrate by printing to obtain a stacked structure of the solder paste and the substrate; b) placing the substrate after printing the copper paste in a drying oven for drying to obtain a pre-dried copper paste substrate; c) using a thermal mounting machine to mount the chip on the pre-dried copper paste substrate to obtain a pre-sintered module; d) placing the pre-sintered module in a vacuum or inert atmosphere for sintering to obtain a power device packaging structure.

10. The patch method according to claim 9, characterized in that: In step a), the printing thickness is 50-150 μm; And / or, in step b), the drying furnace uses air, vacuum or inert gas atmosphere for drying, the drying temperature is 90-110° C., and the drying time is 10-20 min; And / or, in step c), the size of the patch chip is 1*1~5*5mm, the temperature of the lower substrate of the thermal mounting machine is 70-90°C, the temperature of the upper pressure head is 130°C-150°C, and the patch pressure is 5-8kg; And / or, in step d), the sintering conditions are: sintering temperature 180° C.-280° C., sintering pressure 2-20 MPa, and sintering time 3-5 min.

Citation Information

Patent Citations

  • Conductive paste, conductive film-attached base material using the conductive paste, and method for manufacturing conductive film-attached base material

    CN103262173A

  • Copper welding paste for braze welding and preparation method thereof

    CN103659053A

  • Low-temperature sintered nano-copper soldering paste, and preparation method and application method of low-temperature sintered nano-copper soldering paste

    CN114643435A

  • Copper paste for printing capillary structure and preparation method thereof

    CN115954131A

  • Electrode slurry and preparation method thereof

    CN115985549A